2019
DOI: 10.1101/717835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-related Gene Expression Signatures (AGES) in rats demonstrate early, late, and linear transcriptional changes from multiple tissues

Abstract: In order to understand changes in gene expression that occur as a result of age, which might create a permissive or causal environment for age-related diseases, we produced a multitimepoint Age-related Gene Expression Signature (AGES) from liver, kidney, skeletal muscle and hippocampus of rats, comparing 6, 9, 12, 18, 21, 24 and 27-month old animals. We focused on genes that changed in one direction throughout the lifespan of the animal, either early in life (early logistic changes); at mid-age (mid-logistic)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Gene set enrichment analysis (GSEA) and pathway over-representation analysis identified a broad range of pathways related to inflammation and fatty acid metabolism (Figures S5A-S5C) that were upregulated in the livers of aged No ABX mice compared with young adult controls. These data were consistent with previous studies that assessed gene expression in the livers of aged mice (White et al, 2015) and rats (Shavlakadze et al, 2019). Importantly, GSEA also revealed that the expression of genes in a range of pathways and processes associated with metabolism and the immune response were altered in PAM I and PAM II mice compared with No ABX mice (Figures 4B and 4C).…”
Section: Rna Sequencing Reveals Dysregulation Of Liver Metabolism and Immune Function In Pam I And Pam Ii Micesupporting
confidence: 91%
“…Gene set enrichment analysis (GSEA) and pathway over-representation analysis identified a broad range of pathways related to inflammation and fatty acid metabolism (Figures S5A-S5C) that were upregulated in the livers of aged No ABX mice compared with young adult controls. These data were consistent with previous studies that assessed gene expression in the livers of aged mice (White et al, 2015) and rats (Shavlakadze et al, 2019). Importantly, GSEA also revealed that the expression of genes in a range of pathways and processes associated with metabolism and the immune response were altered in PAM I and PAM II mice compared with No ABX mice (Figures 4B and 4C).…”
Section: Rna Sequencing Reveals Dysregulation Of Liver Metabolism and Immune Function In Pam I And Pam Ii Micesupporting
confidence: 91%
“…During this time, a large percentage of the transcriptome undergoes extensive temporal-dependent changes in alternative splicing that occur largely independent of changes in gene expression (Brinegar et al, 2017), suggesting that the temporal changes in protein isoform expression are critical for the post-natal physiological growth of skeletal muscle. In addition, the increasing number of whole transcriptome analyses of physiologically normal, endurance trained, hypertrophic, and atrophying skeletal muscle (Ehmsen et al, 2019;Lindholm et al, 2016;Llano-Diez et al, 2019;Shavlakadze et al, 2019;Wu et al, 2017) provides unique molecular insights into its growth and adaptive responses. Our whole transcriptome analyses describe the changes in gene expression and splicing associated with the myopathy phenotype of Hnrnpu mutants, identifying considerable enrichment for the mis-expression/splicing of genes associated with signal transduction, metabolic processes, and inflammation.…”
Section: Access Isciencementioning
confidence: 99%
“…This notion is supported by a recent study comparing gene expression of age-related biological pathways in different rat tissues, in which hippocampus showed a distinctive transcriptomic profile. In addition to displaying the smallest fold change of upregulated genes, hippocampus demonstrated unaltered gene expression in pathways associated to mitochondrial function that were the most downregulated by aging in other tissues (Shavlakadze et al, 2019). This may reflect that hippocampus is able to uphold mitochondrial integrity and sustain proteostasis upon aging much more efficiently than other tissues.…”
Section: Discussionmentioning
confidence: 96%